2020
DOI: 10.2139/ssrn.3751545
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Price Effects After One-Day of Abnormal Returns in the US Stock Market

Abstract: This paper provides a comprehensive analysis of price effects after one-day abnormal returns and their evolution in the US stock market for the case of Dow Jones Index over the period 1890-2018. Using different statistical tests (both parametrical and non-parametrical) as well as additional technics like modified cumulative abnormal returns approach, regression analysis with dummy variables, R/S analysis and a trading simulation approach; four hypotheses were tested, which are (H 1 ): the after one-day of abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another important issue is whether price patterns differ between normal and crisis periods. For instance, Plastun et al (2022c) provided some evidence of such differences in the case of pre-crisis, post-crisis and crisis periods in the US, Japanese, Chinese, Russian and Brazilian stock markets. Such findings imply that different trading strategies might be appropriate in different periods, an issue which would also be worth investigating in follow-up papers.…”
Section: Discussionmentioning
confidence: 99%
“…Another important issue is whether price patterns differ between normal and crisis periods. For instance, Plastun et al (2022c) provided some evidence of such differences in the case of pre-crisis, post-crisis and crisis periods in the US, Japanese, Chinese, Russian and Brazilian stock markets. Such findings imply that different trading strategies might be appropriate in different periods, an issue which would also be worth investigating in follow-up papers.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, two standard deviations and period 50 are used to calculate abnormal returns. The rationale for this is provided in Plastun et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Their study result revealed positive abnormal returns before the announcement, followed by negative abnormal returns after the announcement. Utilising the Dow Jones Index from 1890 to 2018, Plastun, Sibande, Gupta, & Wohar (2021) thoroughly examined price repercussions following one-day abnormal returns and their evolution in the US stock market. They employed a variety of statistical tests and econometric methodologies.…”
Section: Hypothesis Developmentmentioning
confidence: 99%